2013
DOI: 10.1002/hep.26160
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress plays a major role in chlorpromazine-induced cholestasis in human HepaRG cells

Abstract: Drugs induce cholestasis by diverse and still poorly understood mechanisms in humans. Early hepatic effects of chlorpromazine (CPZ), a neuroleptic drug known for years to induce intrahepatic cholestasis, were investigated using the differentiated human hepatoma HepaRG cells. Generation of reactive oxygen species (ROS) was detected as early as 15 minutes after CPZ treatment and was associated with altered mitochondrial membrane potential and disruption of the pericanalicular distribution of F-actin. Inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 35 publications
13
89
3
Order By: Relevance
“…Indeed, the accumulation of CPZ inside the cells was relatively important in primary rat hepatocytes exposed to 20 lM CPZ and in HepaRG cells exposed to 15 lM CPZ. Chlorpromazine has been shown to induce phospholipidosis in vivo (Anderson and Borlak, 2006;Tavoloni and Boyer, 1980) and in vitro (Anthérieu et al, 2013;Bachour-El Azzi et al, 2014) and to bind to lamellar bodies that are formed during phospholipidosis (Joshi et al, 1989). In our experiments, lamellar bodies were observed after the 14-day repeated exposure of HepaRG cells to 15 lM CPZ and of primary rat hepatocytes to 20 lM of CPZ (not shown).…”
Section: Discussioncontrasting
confidence: 40%
“…Indeed, the accumulation of CPZ inside the cells was relatively important in primary rat hepatocytes exposed to 20 lM CPZ and in HepaRG cells exposed to 15 lM CPZ. Chlorpromazine has been shown to induce phospholipidosis in vivo (Anderson and Borlak, 2006;Tavoloni and Boyer, 1980) and in vitro (Anthérieu et al, 2013;Bachour-El Azzi et al, 2014) and to bind to lamellar bodies that are formed during phospholipidosis (Joshi et al, 1989). In our experiments, lamellar bodies were observed after the 14-day repeated exposure of HepaRG cells to 15 lM CPZ and of primary rat hepatocytes to 20 lM of CPZ (not shown).…”
Section: Discussioncontrasting
confidence: 40%
“…This means that the time-scales of inhibition and recovery as well as the extent of inhibition during and after CsA treatment can be uniquely determined from the time-course experiments for the three membrane containing transporters. CPZ which is an inhibitor of cellular uptake and canalicular export but not sinusoidal export (Antherieu, et al, 2013) was found to act on TCA clearance rates more slowly when compared to CsA. In agreement, by parameter estimation we could show that inhibition by CPZ is irreversible, the two reaction parameters corresponding to reversibility being compatible with zero.…”
Section: Discussionsupporting
confidence: 73%
“…In agreement, by parameter estimation we could show that inhibition by CPZ is irreversible, the two reaction parameters corresponding to reversibility being compatible with zero. Indeed, experimental studies showed that the cholestatic mechanism of CPZ is indirect and slower, depending on generation of reactive oxygen species that lead to irreversible bile flow inhibition (Antherieu, et al, 2013). This…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2h incubation cells were washed and then scraped in 0.1N NaOH. The remaining radiolabeled substrate was measured through scintillation counting to determine TA efflux (Antherieu et al, 2013).…”
Section: Taurocholic Acid Effluxmentioning
confidence: 99%